BEHAVIORAL REACTIONS PENGGUNA FACEBOOK PADA PERSONALIZED FACEBOOK ADS - Taufiq Gunawan; I Made Bayu Dirgantara; Bimo Suryo Wicaksono (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to determine the reaction of Facebook users when they see personalized ads on Facebook. Data obtained leads to characteristics of ads that are liked by the user. Qualitative methods combined with think aloud and observation techniques result in a deep understanding of what the users think when they see ads on Facebook, how they respond to those ads, and why they react in certain ways. Semi-structured interviews with open-ended questions were conducted with 12 subjects. The analysis technique is processed through data reduction and then conclusions are drawn by triangulation to produce valid results. The results are based on the model of the effects of perceived personalization which are the behavioral reactions (ad attitude, ad avoidance, ad credibility, and ad skepticism). Ads that are liked by the users have characteristics of relevance; interesting content; easy to understand context; arouse curiosity; and provide offers such as discounts or promos.